Isolation, Structure, Chemistry and Photochemistry of cis?bis(2,2'-bipyridyl)carbonylchlororuthenium(II) perchlorate - KELLY, JOHN MOFFAT (My University, 1980)
The molecular structure and chemical and photochemical reactions of [Ru(bpy)2(CO)Cl]+ClO4?, which has been isolated from the reaction of ruthenium trichloride and 2,2?-bipyridyl(bpy) in dimethylformamide, are described.
PUBLISHED
Keywords: [Ru(bpy)2(CO)Cl]+ClO4?; [Ru(bpy)2(CO)Cl]+ClO4?